Institutionalization of administrative arbitration: especially in the field of public contracts (De Legibus - Law Journal, 2024)
With the emergence of new aspects in the field of Administrative Litigation, an analysis of the regime of institutionalization of administrative arbitration is necessary, the importance of which is truly considerable.Based on this exposition, an attempt is made to differentiate the institutionalization of arbitration both at a general level and in matters of public contracts. For this, it is evident the need to analyze the fulfillment of requirements for the admission of arbitration in matters of ad hoc public contracts.To this end, a detailed observation is proposed with regard to two important precepts within administrative arbitration: article 187 of the CPTA and article 476 of the CCP.
Keywords: institutionalization; administrative law; public procurement; ad hoc arbitration; CCP; CPTA; required arbitration.